Adverse differences in cardiometabolic risk factor levels between individuals with pre-diabetes and normal glucose metabolism are more pronounced in women than in men: the Maastricht Study - Michiel L Bots; Mark Woodward; Rimke C Vos; Rianneke de Ritter; Simone J S Sep; Carla J H van der Kallen; Miranda T Schram; Abraham A Kroon; Marleen M J van Greevenbroek; Simone J P M Eussen; Pieter C Dagnelie; Marit de Jong; et al. (BMJ Open Diabetes Research & Care)
Objective To investigate whether adverse differences in levels of cardiovascular risk factors in women than men, already established when comparing individuals with and without diabetes, are also present before type 2 diabetes onset.Research design and methods In a population-based cohort study of individuals aged 40-75 years (n=3410; 49% women, 29% type 2 diabetes (oversampled by design)), we estimated associations with cardiometabolic and lifestyle risk factors of (1) pre-diabetes and type 2 diabetes (reference category: normal glucose metabolism) and (2) among non-diabetic individuals, of continuous levels of hemoglobin A1c (HbA1c). Age-adjusted sex differences were analyzed using linear and logistic regression models with sex interaction terms.Results In pre-diabetes, adverse differences in cardiometabolic risk factors were greater in women than men for systolic blood pressure (difference, 3.02 mm Hg; 95% CI:−0.26 to 6.30), high-density lipoprotein (HDL) cholesterol (difference, −0.10 mmol/L; 95% CI: −0.18 to −0.02), total-to-HDL cholesterol ratio (difference, 0.22; 95% CI: −0.01 to 0.44), triglycerides (ratio: 1.11; 95% CI: 1.01 to 1.22), and inflammation markers Z-score (ratio: 1.18; 95% CI: 0.98 to 1.41). In type 2 diabetes, these sex differences were similar in direction, and of greater magnitude. Additionally, HbA1c among non-diabetic individuals was more strongly associated with several cardiometabolic risk factors in women than men: per one per cent point increase, systolic blood pressure (difference, 3.58 mm Hg; 95% CI: −0.03 to 7.19), diastolic blood pressure (difference, 2.10 mm Hg; 95% CI: −0.02 to 4.23), HDL cholesterol (difference, −0.09 mmol/L; 95% CI: −0.19 to 0.00), and low-density lipoprotein cholesterol (difference, 0.26 mmol/L; 95% CI: 0.05 to 0.47). With regard to lifestyle risk factors, no consistent pattern was observed.Conclusion Our results are consistent with the concept that the more adverse changes in cardiometabolic risk factors in women (than men) arise as a continuous process before the onset of type 2 diabetes.